Synchronous grouting material for low-carbon impervious shield tunnel and preparation method of synchronous grouting material
By using low-carbon composite cementitious materials and fine aggregates to prepare synchronous grouting materials, the lack of performance and high carbon emission problems of cement-based synchronous grouting materials in tunnel construction are solved, and efficient and environmentally friendly tunnel construction materials are achieved.
Patent Information
- Application Number
- CN202411356332.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-03-11
AI Technical Summary
The existing cement-based synchronous grouting materials have problems such as high hydration heat, easy to produce cracks, insufficient seepage resistance and density in tunnel construction. At the same time, the cement production process consumes a large amount of energy and generates a large amount of carbon emissions.
Synchronous grouting materials are prepared by collaborative compatibility of low-carbon composite cementitious materials and fine aggregates, and the material composition includes low-carbon composite cementitious materials, fine aggregates, mud, water and admixtures. By adjusting the proportion of each component and adding admixtures, the mechanical properties and anti-seepage properties of the material are improved.
It has achieved the reduction of cement and river sand usage, reduced energy consumption and carbon emissions, improved the mechanical properties, impermeability and density of synchronous grouting, and met the stability and safety requirements of tunnel construction.
Smart Images

Figure CN119591357A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tunnel construction materials, in particular to a synchronous grouting material for a low-carbon anti-permeability shield tunnel and a preparation method thereof. Background Art
[0002] During the shield excavation process of urban tunnels, synchronous grouting is widely used in tunnel construction because it can reduce surface deformation and tunnel settlement, in order to maintain the stability of the tunnel project and ensure the safety of tunnel construction. According to different construction conditions, the commonly used synchronous grouting materials behind the shield tunnel wall can be mainly divided into two categories: single-liquid type and double-liquid type. At present, single-liquid materials are more widely used. The main raw materials are cement, natural river sand, bentonite, fly ash and admixtures, among which natural river sand is the largest, accounting for 70%-80%. However, with the limited excavation of rivers and the improvement of national environmental protection requirements, natural river sand resources are becoming increasingly scarce. The development of solid waste resource utilization has become an effective way to solve the contradiction between resource depletion, reducing carbon emissions and economic construction needs.
[0003] At present, the commonly used synchronous grouting material is cement-based synchronous grouting. Cement has high hydration heat and is prone to cracks, which affects the anti-permeability and grouting density of the synchronous grouting. It is also not very effective in shield tunneling conditions in water-rich strata. At the same time, the cement production process consumes a lot of energy and produces a lot of carbon emissions. Therefore, the use of solid waste to develop low-carbon and anti-permeability synchronous grouting materials for shield tunnels can not only reduce carbon emissions, but also achieve low-carbon green development in the transportation field. Summary of the invention
[0004] The purpose of the present invention is to provide a low-carbon and anti-seepage synchronous grouting material for shield tunnels and a preparation method thereof, so as to solve the problem that the commonly used synchronous grouting material proposed in the above background technology is cement-based synchronous grouting, the cement has high hydration heat, is prone to cracks, affects the anti-seepage performance and grouting density of the synchronous grouting, and is not effective in shield tunneling conditions in water-rich strata. At the same time, the cement production process consumes a large amount of energy and generates a large amount of carbon emissions.
[0005] To achieve the above object, the present invention provides the following technical solution: a synchronous grouting material for a low-carbon impermeability shield tunnel, wherein the synchronous grouting material for a low-carbon impermeability shield tunnel is mainly composed of a low-carbon composite cementitious material, fine aggregate, mud, water and an admixture, wherein the mass ratio of the total mass of the low-carbon composite cementitious material and the fine aggregate to the mud (on a dry basis) is 0.1-0.6, the proportion of water used in the low-carbon composite cementitious material (water-binder ratio) is 0.5-2.5, and the amount of the admixture added does not exceed 0.5%;
[0006] The low-carbon composite cementitious material comprises, by weight, 5-20% cement, 10-40% steel slag powder, 20-50% mineral powder, and 20-40% fly ash, wherein:
[0007] The cement is silicate cement with a P·O4 of 2.5;
[0008] The steel slag powder is converter steel slag treated by hot stewing method, and has a specific surface area of ≥450m2 / kg;
[0009] The mineral powder is S95 grade mineral powder with a specific surface area of ≥400m2 / kg;
[0010] The fly ash is low-calcium fly ash, and the 28d strength activity index is ≥70%.
[0011] Preferably, the radioactive specific activities of the natural radionuclides radium-226, thorium-232 and potassium-40 in the fly ash simultaneously satisfy IRa≤1.0 and Iγ≤1.0.
[0012] Preferably, the fine aggregate is 0-5 mm construction waste fine aggregate (waste concrete or decoration waste) and river sand, wherein the fineness modulus of the construction waste fine aggregate is 2.5-2.8, the mass ratio of the construction waste fine aggregate to the river sand is (20-60): (40-80), and the mass proportion is 70-90%.
[0013] When waste concrete and river sand are used as fine aggregate, the preferred ratio of waste concrete to river sand is 0.4-0.6. When decoration waste and river sand are used as fine aggregate, the preferred ratio of decoration waste to river sand is 0.6-1.
[0014] Preferably, the mud content or stone powder content of the fine aggregate is ≤7.0%.
[0015] Preferably, the mud is one or more of engineering mud, dredging mud, municipal sludge, and the water content should be controlled within 60%.
[0016] Preferably, the mud is one or more of engineering mud, dredging mud, municipal sludge, etc. The mud can be mixed with fine aggregate in a mass ratio of (0-30): (70:100).
[0017] Preferably, the admixture includes one or more of polycarboxylate water reducer, attapulgite, starch ether, and cellulose ether, and the admixture dosage is 0-0.5%.
[0018] A low-carbon anti-permeability synchronous grouting material for a shield tunnel and a preparation method thereof, comprising the following steps:
[0019] S1. Weigh each raw material according to weight ratio;
[0020] S2. Mix cement, steel slag powder, mineral powder, fly ash, fine aggregate and mud in proportion, and then pour weighed water, admixtures, etc. into the mixture to prepare a low-carbon and anti-seepage synchronous grouting material for shield tunnels.
[0021] Compared with the prior art, the invention has the following beneficial effects: the low-carbon anti-permeability type synchronous grouting material for shield tunnels is
[0022] 1. The low-carbon and impermeable synchronous grouting material for shield tunnel can ensure the coating effect of cementitious materials and reduce the amount of cement and river sand, so as to achieve the purpose of energy conservation and emission reduction. When waste concrete, decoration waste or river sand or two or more of them are used as fine aggregates for preparing synchronous grouting materials, the fine aggregates should be tested for particle grading, fineness modulus and mud or stone powder content to ensure that the fineness modulus of the construction waste fine aggregate is 2.5-2.8, and the mud or stone powder content should be controlled within 7.0%. The construction waste fine aggregate screened by the above method can be used to prepare synchronous grouting materials to avoid poor coating effect of cementitious materials due to excessive fineness or coarseness of fine aggregates, and to avoid excessive mud or stone powder content that is unfavorable to the mechanical properties of synchronous grouting, affecting fluidity and construction performance.
[0023] 2. The low-carbon and anti-seepage synchronous grouting material for shield tunnels can achieve the purpose of improving the mechanical properties, anti-seepage properties and grouting density of synchronous grouting. The low-carbon composite cementitious material is prepared by synergistically combining multi-source solid wastes such as cement, steel slag powder, mineral powder and fly ash. It can not only improve the mechanical properties of the synchronous grouting material, but also synergistically use waste concrete or decoration waste as fine aggregate. The stone powder content in it can improve the density of the synchronous grouting and has better anti-seepage properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 It is a schematic diagram of technical performance indicators of the synchronous grouting materials of Examples 1-7 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Example 1
[0027] A synchronous grouting material for a low-carbon, anti-seepage shield tunnel mainly consists of a low-carbon composite cementitious material, fine aggregate, water and an admixture. The low-carbon composite cementitious material consists of cement, steel slag powder, mineral powder and fly ash. The fine aggregate is a mixture of waste concrete and river sand, or a mixture of decoration waste and river sand, or all decoration waste.
[0028] The low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 5% cement, 30% steel slag powder, 40% mineral powder, and 25% fly ash. The fine aggregate is waste concrete and river sand, and the mass ratio is 20:80. The fineness modulus is 2.7. The mass ratio of the low-carbon composite cementitious material to the fine aggregate (mortar-sand ratio) is 0.6, the water-cement ratio is 0.55, and the admixture is polycarboxylate water reducer and starch ether, and the admixture is 0.05%. The above materials are mixed according to the mass ratio to obtain the synchronous grouting material.
[0029] Example 2
[0030] Compared with Example 1, the difference is that the fine aggregate is waste concrete and river sand, the mass ratio of which is 60:40, the measured fineness modulus is 2.6, the mass ratio of low-carbon composite cementitious material and fine aggregate (cement-sand ratio) is 0.4, the water-cement ratio is 0.8, and the admixtures are polycarboxylate water reducer and starch ether, and the addition amount is 0.1%;
[0031] The remaining preparation steps and component requirements remain the same as those in Example 1.
[0032] Example 3
[0033] Compared with Example 1, the difference is that the low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 20% cement, 10% steel slag powder, 30% mineral powder, 40% fly ash, and the fine aggregate is waste concrete and river sand, the mass ratio of which is 50:50, the measured fineness modulus is 2.6, the mass ratio of the low-carbon composite cementitious material to the fine aggregate (cement-sand ratio) is 0.2, and the water-cement ratio is 0.7. The admixtures are polycarboxylate water reducer and cellulose ether, and the dosage is 0.08%;
[0034] The remaining preparation steps and component requirements remain the same as those in Example 1.
[0035] Example 4
[0036] Compared with Example 1, the difference is that the low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 5% cement, 40% steel slag powder, 30% mineral powder, 25% fly ash, and the fine aggregate is decoration waste and river sand, the mass ratio of which is 30:70, the measured fineness modulus is 2.5, the mass ratio of the low-carbon composite cementitious material to the fine aggregate (cement-sand ratio) is 0.4, and the water-cement ratio is 0.7. The admixtures are polycarboxylate water reducer and cellulose ether, and the dosage is 0.06%;
[0037] The remaining preparation steps and component requirements remain the same as those in Example 1.
[0038] Example 5
[0039] Compared with Example 1, the difference is that the low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 5% cement, 40% steel slag powder, 30% mineral powder, 25% fly ash, and the fine aggregate is decoration waste and river sand, the mass ratio of which is 80:20, the measured fineness modulus is 2.7, the mass ratio of the low-carbon composite cementitious material to the fine aggregate (cement-sand ratio) is 0.2, and the water-cement ratio is 2.0. The admixture is cellulose ether, and the dosage is 0.1%;
[0040] The remaining preparation steps and component requirements remain the same as those in Example 1.
[0041] Example 6
[0042] Compared with Example 1, the difference is that the low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 15% cement, 35% steel slag powder, 25% mineral powder, 25% fly ash, and the fine aggregate is decoration waste and river sand, the mass ratio of which is 50:50, the measured fineness modulus is 2.6, the mass ratio of the low-carbon composite cementitious material to the fine aggregate (cement-sand ratio) is 0.1, and the water-cement ratio is 1.2. The admixture is cellulose ether, and the dosage is 0.05%;
[0043] The remaining preparation steps and component requirements remain the same as those in Example 1.
[0044] Example 7
[0045] Compared with Example 1, the difference is that the low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 10% cement, 35% steel slag powder, 30% mineral powder, 25% fly ash, the fine aggregate is decoration waste, the fineness modulus is measured to be 2.8, the mass ratio of the low-carbon composite cementitious material to the fine aggregate (mortar-sand ratio) is 0.1, the water-cement ratio is 1.1, and the admixtures are polycarboxylate water reducer, attapulgite, and cellulose ether, and the admixture amount is 0.08%;
[0046] The remaining preparation steps and component requirements remain the same as those in Example 1.
[0047] Example 8
[0048] Compared with Example 1, the difference is that the low-carbon composite cementitious material is prepared according to the following mass percentages of the components: 5% cement, 30% steel slag powder, 40% mineral powder, and 25% fly ash. The fine aggregate is waste concrete and river sand, and the mass ratio is 20:80. The fineness modulus is 2.7. The mass ratio of the low-carbon composite cementitious material to the fine aggregate (mortar-sand ratio) is 0.6, wherein the mass of the mud (on a dry basis) accounts for 30% of the mass of the fine aggregate, the water-binder ratio is 2.2, and the admixture is polycarboxylate water reducer and starch ether, and the admixture is 0.05%. The above materials are mixed according to the mass ratio to obtain the synchronous grouting material.
[0049] Comparative Example 1
[0050] The synchronous grouting materials for shield tunnels are prepared with the synchronous grouting raw materials commonly used in the market: cement and fly ash are used as cementitious materials, 0-5mm natural sand is used as fine aggregate, the fineness modulus is measured to be 2.6, the mass ratio of cementitious materials to fine aggregate (cement-sand ratio) is 0.4, the water-binder ratio is 0.6, and the admixture is bentonite, with a dosage of 10%;
[0051] The remaining preparation steps and component requirements are the same as those in Example 1.
[0052] Comparative Example 2
[0053] The method of single-mixing mineral powder is adopted, with cement and mineral powder as cementitious materials, fine aggregate is waste concrete and river sand, and the mass ratio is 50:50. The fineness modulus is measured to be 2.7, the mass ratio of low-carbon composite cementitious material and fine aggregate (mortar-sand ratio) is 0.4, the water-cement ratio is 0.6, and the admixtures are polycarboxylic acid water-reducing agent and cellulose ether, and the addition amount is 0.05%. The above materials are mixed according to the mass ratio to obtain the synchronous grouting material.
[0054] Comparative Example 3
[0055] The method of single addition of steel slag powder is adopted, cement and steel slag powder are used as cementitious materials, fine aggregate is waste concrete and river sand, the mass ratio of which is 50:50, the fineness modulus is measured to be 2.6, the mass ratio of low-carbon composite cementitious material and fine aggregate (mortar-sand ratio) is 0.6, the water-cement ratio is 0.5, the admixtures are polycarboxylic acid water reducer and cellulose ether, the addition amount is 0.05%, and the above materials are mixed according to the mass ratio to obtain the synchronous grouting material.
[0056] For detailed test results, see Figure 1 , Figure 1 These are the technical performance indicators of the synchronous grouting materials of Examples 1-7 and Comparative Examples 1-3.
[0057] Depend on Figure 1 It can be seen that the properties of the prepared synchronous grouting material, such as consistency, consistency loss over time, fluidity, fluidity loss over time, water seepage rate, compressive strength, water-land strength ratio and stone rate, meet the requirements of T / CECS563-2018 "Technical Code for Application of Synchronous Grouting Materials in Shield Tunnels".
[0058] In summary, the low-carbon and anti-seepage synchronous grouting material for shield tunnels and its preparation method have achieved the purpose of ensuring the grouting effect of cementitious materials, reducing the amount of cement and river sand, achieving energy conservation and emission reduction, and improving the mechanical properties, anti-seepage properties and grouting density of synchronous grouting, thus meeting people's usage needs.
[0059] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. Low-carbon anti-permeability synchronous grouting material for shield tunnel, characterized by: The synchronous grouting material for low-carbon anti-permeability shield tunnel mainly consists of low-carbon composite cementitious material, fine aggregate, mud, water and admixture, wherein the mass ratio of low-carbon composite cementitious material to fine aggregate is 0.1-0.6, the proportion of water used in low-carbon composite cementitious material (water-binder ratio) is 0.5-2.5, and the addition amount of the admixture does not exceed 0.5%; The low-carbon composite cementitious material comprises, by weight, 5-20% cement, 10-40% steel slag powder, 20-50% mineral powder, and 20-40% fly ash, wherein: The cement is silicate cement with a P·O4 of 2.5; The steel slag powder is converter steel slag treated by hot stewing method, and has a specific surface area of ≥450m2 / kg; The mineral powder is S95 grade mineral powder with a specific surface area of ≥400m2 / kg; The fly ash is low-calcium fly ash, and the 28d strength activity index is ≥70%.
2. According to claim 1, the low-carbon anti-permeability synchronous grouting material for shield tunnel is characterized by: The radioactivity specific activities of the natural radionuclides radium-226, thorium-232 and potassium-40 in the fly ash simultaneously satisfy IRa≤1.0 and Iγ≤1.
0.
3. The low-carbon anti-permeability synchronous grouting material for shield tunnel according to claim 1 is characterized in that: The fine aggregate is 0-5 mm construction waste fine aggregate (waste concrete or decoration waste) and river sand, wherein the fineness modulus of the construction waste fine aggregate is 2.5-2.8, the mass ratio of the construction waste fine aggregate to the river sand is (20-60): (40-80), and the mass proportion is 70-90%.
4. The low-carbon anti-permeability synchronous grouting material for shield tunnel according to claim 1 is characterized by: The mud content or stone powder content of the fine aggregate is ≤7.0%.
5. The low-carbon anti-permeability synchronous grouting material for shield tunnel according to claim 1 is characterized in that: The mud is one or more of engineering mud, dredging mud, municipal sludge, and the water content should be controlled within 60%.
6. The low-carbon anti-permeability synchronous grouting material for shield tunnel according to claim 1 is characterized by: Mud can be mixed with fine aggregate in a mass ratio of (0-30):(70:100).
7. The low-carbon anti-permeability synchronous grouting material for shield tunnel according to claim 1 is characterized by: The admixture comprises one or more of polycarboxylate water reducer, attapulgite, starch ether and cellulose ether, and the admixture dosage is 0-0.5%.
8. Low-carbon impermeability type synchronous grouting material for shield tunnel and its preparation method, applied to the low-carbon impermeability type synchronous grouting material for shield tunnel according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Weigh each raw material according to weight ratio; S2. Mix cement, steel slag powder, mineral powder, fly ash, fine aggregate and mud in proportion, and then pour weighed water, admixtures, etc. into the mixture to prepare a low-carbon and anti-seepage synchronous grouting material for shield tunnels.
Citation Information
Cited By
Low-carbon solid waste-based shield mortar as well as preparation method and application thereof
CN117776641A